Jamaican Gold - Jamaican Sprinters (University of the West Indies Press, 2010)
Book about the success of Jamaican runners, and why Jamaicans run so fast. Written for sport and athletic fans in particular, Jamaicans at home and abroad, and fans of Jamaica.